Volunteers helped to ease sufferings of flood victims - UMP, PNC

(untitled)
Despite hectic schedules and preparations ahead of the final exams, it did not stop a group of 45 Universiti Malaysia Pahang (UMP) undergraduates to be volunteers assisting flood victims in a programme organised by UMP Student Representative Council (SRC) on Dec 29, 2012.